Knockdown of MUC16 (CA125) Enhances the Migration and Invasion of Hepatocellular Carcinoma Cells - Huang, Yao; Huang, Xiaoyu; Zeng, Jianxing; Lin, Jun (Frontiers in Oncology, 2021)
Hepatocellular carcinoma (HCC) has been recognized as the most frequent primary liver cancer and a leading cause of death among patients with cirrhosis worldwide. Surveillance of HCC using serum markers aims to reduce the disease-related mortality of HCC. MUC16 (mucin 16, also known as carbohydrate antigen 125, CA125) has been predicted as a tumour biomarker for many cancer types. Based on the high frequency mutation rate in a database from the Cancer Genome Atlas (TCGA), we investigated the effects of MUC16 knockdown and the regulatory profile of MUC16 in HepG2 and Huh7 cell lines. Knockdown of MUC16 was conducted via siRNA transfection, and the proliferation of cells was not affected by CCK8 assay results. Moreover, decreasing the expression of MUC16 enhanced the migration and invasion of cells, as shown by wound healing and transwell assays. Furthermore, RNA-seq was used to investigate the effects of MUC16 knockdown on the gene expression profile of hepatocellular carcinoma cells, and the tumour-related gene TP53INP2 was identified as a possible downstream gene regulated by MUC16. Our study demonstrated the significant role of MUC16 in the inhibition of the migration and invasion of hepatocellular carcinoma cells.